Titanium tert-butyl- and trimethylsilyl-imido complexes with monopendant arm triazacyclononane ligands. - Gardner, J; Robson, D; Rees, L; Mountford, P (2001)
Neutral and cationic titanium imido complexes (R = t-Bu or SiMe 3) with a triazacyclononane ligand bearing a monopendant arm have been synthesized. The structures of [Ti(NSiMe 3)(L 1)Cl] and [Ti(NBu t)(L 2)Cl]Cl are reported where HL 1 =1-(2-hydroxy-3,5-di-tert-butylbenzyl)-4,7-diisopropyl-1,4,7-tria zacyclononane and L 2 = 1-(2-pyridylmethyl)-4,7-diisopropyl-1,4,7-triazacyclononane.